2016
DOI: 10.17582/journal.bjv/2016.3.4.105.114
|View full text |Cite
|
Sign up to set email alerts
|

Where is the Participation in Participatory Epidemiology? How Engagement with Social Science could lead to Improved Understanding and Control of Peste des Petits Ruminants

Abstract: | Peste des Petits ruminants (PPR) is a potentially lethal, highly contagious viral disease of sheep and goats. Domestic sheep and goats are important species for the livelihoods of poor people in many developing countries. Within societies where PPR is now spreading, poverty is widespread and the disease is expected to have significant negative impacts on livelihoods. In resource-constrained marginalised societies, it is often difficult to collect disease data in conventional ways. Participatory epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The importance of engaging the affected groups (i.e. the animal owners) in the goal to eradicate PPR has also been emphasized ( 43 ). Most of the southern African countries are free from PPR, with the current southern border of confirmed presence of PPR being – from west to east – Angola, DRC, and Tanzania ( 18 ).…”
Section: Implications Of Ppr In Tanzaniamentioning
confidence: 99%
“…The importance of engaging the affected groups (i.e. the animal owners) in the goal to eradicate PPR has also been emphasized ( 43 ). Most of the southern African countries are free from PPR, with the current southern border of confirmed presence of PPR being – from west to east – Angola, DRC, and Tanzania ( 18 ).…”
Section: Implications Of Ppr In Tanzaniamentioning
confidence: 99%
“…PE in veterinary science has been developed as a tool for collecting epidemiological data in contexts where conventional quantitative data are unavailable. However, recent research has shown that the focus on being accepted by the conventional veterinary research community has led to “participation” in PE, and the resulting relevance of the findings to local people, being rather limited ( 14 ). In this study, we as authors combined our expertise in veterinary medicine and rural development studies, respectively, while remaining equally open to local competence, drawing on participatory methods.…”
Section: Introductionmentioning
confidence: 99%
“…As the success of the eradication efforts will greatly depend on farmers' willingness to participate in vaccination and surveillance programmes, as demonstrated during the rinderpest eradication programme ( 8 ), greater consideration must be given to research in social sciences ( 9 ). The achievement of this international programme also requires economic perspectives ( 10 ).…”
mentioning
confidence: 99%